How forward looking are consumers? Further evidence for the United States. - Himarios, Daniel (Southern Economic Journal, 2000)
A modified version of a standard model of consumption is developed to test how forward looking consumers are. The model supports the existence of both rule-of-thumb consumers and consumers who are, to some degree, myopic with regard to their future income and taxes. However, the model assumes that this latter set of consumers is behaving in a manner that is “boundedly rational,” whereas consumers' quasi-myopic behavior actually derives from many sources and does not necessarily mean that they are not optimizing. The model suggests that the simple permanent income hypothesis fails to accurately describe consumer behavior. The model was tested using data for the United States for the period 1951–1990 and evidence of myopic behavior among consumers was found.